THE IMPLEMENTATION OF ASSERTIVE TRAINING TECHNIQUE TO ENHANCE THE SELF-CONFIDENCE OF JUNIOR HIGH SCHOOL STUDENTS IN KARANGANYAR REGENCY - asrowi - -; Chadijah - -; Ferisa Prasetyaning Utami (Pondok Pesantren Modern Islam Assalaam, 2017)
This research was a research and development. The purposes of this research were to investigate the validity of the product based on the experts, to investigate the advisability based on practitioners’ test and to investigate the effectiveness of the implementation of assertive training technique guidance to enhance junior high school students’ self-confidence. The examination of the effectiveness of the product was conducted by using Matching Pretest-Posttest Control Group Design experimental design. The data collection techniques used were questionnaire, observation, and interview. The subject of this research was the seventh grade students of SMP Negeri Karanganyar. This research resulted a product in the form of assertive training technique guidance which had been examined by the experts and practitioners and its effectiveness had been experimented to the students. The result of the experts’test was that the product had valid category with minor revision with 83,9 % score .The result of the practitioners’ test was that the product had valid category with minor revision with 84.6% score. Furthermore, the effectiveness of the product was examined in limited range towards the research subject. The activities conducted towards the subject included giving pretest, implementing the product, and giving posttest. The effectiveness examination result showed that there was an improvement in the average score before and after the treatment was given, that were 90.8 of average pretest score and 103.07 of average posttest score. It was supported by the statistical analysis result by using SPPS.16 with Wilcoxon test that showed that the significance score was <0.005 (0.001< 0.05), so that it could be concluded that H0 was denied which meant that there was a difference between the score in the pretest and the score in the posttest of the experimental group. It showed that there was improvement in students’ self-confidence as the result of the implementation of assertive training technique guidance. Thus it could be concluded that assertive training technique guidance was effective to enhance the self-confidence of the students in SMP Negeri in Karanganyar